Reinventing Performance Management - Crews, Derek (Archives of Business Research, 2021)
Performance appraisals have traditionally been conducted annually or semi-annually. Recently, many companies are transitioning to ongoing feedback and coaching, either in addition to periodic appraisals, or lieu of them. There have also been calls for completely reinventing performance management systems, as the result of an abundance of research that indicates performance processes are over-engineered and time-consuming, and they tend to demotivate employees while hindering candid and honest conversations. This paper examines the common problems with attribution error and rater bias in traditional performance appraisal systems. Five mini-case studies are then presented by exploring how five large companies (Netflix, Adobe, Deloitte, IBM, GE), have reinvented the way in which performance management is implemented. The paper examines why these companies moved away from traditional performance appraisal and what processes replaced it. The paper also identifies emerging trends that will impact the future of performance management and offers suggestions for the road ahead.